Comparative proteome analysis reveals that blood and sugar meals induce differential protein expression in Aedes aegypti female heads. Issue 19 (5th August 2016) - Nunes, Alessandra T.; Brito, Nathalia F.; Oliveira, Daniele S.; Araujo, Gabriel D. T.; Nogueira, Fabio Cesar S.; Domont, Gilberto B.; Moreira, Monica F.; Moreira, Leandro M.; Soares, Marcia R.; Melo, Ana C. A.
Abstract : Aedes aegypti females ingest sugar or blood to obtain the nutrients needed to maintain cellular homeostasis. During human blood ingestion, female mosquitoes may transmit different viruses such as dengue, yellow fever and, more recently, zika and chikungunya. Here, we report changes in protein expression in the heads of adult female Ae. aegypti mosquitoes in response to the ingestion of blood or sugar. Proteins extracted from the heads of Ae. aegypti fed exclusively on blood (BF) or sugar (SF) were trypsin hydrolyzed (off‐gel) and analyzed by the reverse‐phase nano‐liquid chromatography coupled with hybrid mass spectrometry. A total of 1139 proteins were identified in female heads, representing 7.4% of the predicted proteins in Ae. aegypti genome (total = 15 419 active genes). Gene ontology annotation and categories showed that, in this insect, the head was rich in proteins involved in the metabolic process, proton transport, organelle, macromolecular complex, structural molecule activity, antioxidant activity, and catalytic activity. Our report is the first indicating that many of the annotated genes are translated into functional proteins in heads of adult female Ae. aegypti . Interestingly, we identified 8.7 times more exclusively expressed proteins involved in signal transduction, replication–transcription–translation (5.5 x), and transport (2.9 x) activity in BF than in SF groups. This paper discusses the protein profile of Ae. aegypti female heads and its implications for blood ingestion and carbohydrate intake.